Educators' learning experiences and intention to use online learning management systems’ platforms: a perceptual study - Singh, Shruti; Chakraborty, Anindita (Serbian Journal of Management, 2024)
This study examines the adoption and use of Online Learning Management Systems (OLMS) in central government universities in India, emphasizing the impact of instructors' previous online learning experiences. To accomplish this, we employed the Technology Acceptance Model as the theoretical foundation, expanding its scope to encompass external factors and perceived variables related to O-LMS adoption. We investigate OLMS adoption patterns, platform preferences, and the impact of ownership status on technological integration using survey data obtained from faculty members at the top ten central government universities. Through a rigorous survey conducted among 326 faculty respondents from esteemed institutions and universities, we delved into their experiences, challenges, and perceived benefits associated with O-LMS utilization. Our data show that Moodle is the most widely used OLMS platform, with 85% of surveyed universities using this open-source system. Furthermore, we identify the important impact that educators' prior online learning experiences have in molding their opinions of OLMS, emphasizing the need for extensive training and continuous support programs. Furthermore, our findings highlight the need for further research to investigate the efficacy of various OLMS platforms, longitudinal studies to track the long-term effects of adoption, and qualitative investigations into educators' perspectives and experiences. By focusing on these research directions, stakeholders can improve technology integration in educational settings, resulting in more effective and inclusive learning environments.
Keywords: O-LMS; learning management system; perceived online learning experience; TAM